Pengembangan Media Pembelajaran Berbasis Video Animasi Stop Motion Pada Tema 6 Subtema 2 “Perpindahan Kalor Di Sekitar Kita” Kelas V SDN 173468 Pulogodang T.A 2022/2023 - Sri Devi Simanullang; Wildansyah Lubis (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research was conducted based on the problems experienced in the learning process, namely conventional learning methods and rarely using learning media which causes students to feel bored and less interested in following the learning process without using learning media in the learning process in class. Students are more interested in learning media that displays moving images and sound (audiovisual/video). The purpose of this study was to: (1) to see the validity level of Stop Motion Animation Video Learning Media on Theme 6 Sub-theme 2 "Heat Transfer Around Us" Grade V Students at SDN 173468 Pulogodang T.A 2022/2013. (2) to see the practicality of Stop Motion Video Learning Media in Theme 6 Sub-theme 2 "Heat Transfer Around Us" Class V Students of SDN 173468 Pulogodang T.A 2022/2023, (3) to determine the level of effectiveness of learning from the results of the Development of Stop Motion Video Learning Media on Theme 6 Sub-theme 2 "Heat Transfer Around Us" Class V Students of SDN 173468 Pulogodang T.A 2022/2023. The research location for SDN 173468 Pulogodang Class V, Pakkat District, Humbang Hasundutan Regency, consisted of 17 students. .This research is a type of R&D (Research and Development) research with the ADDIE development model which has 5 stages including: Analysis, Design, Development, Implementation, and Evaluation. When the research was carried out from May to July 2023. The data collection techniques used were observation, interviews, validation sheet questionnaires and tests. Data analysis techniques were performed using quantitative descriptive analysis.The results of the study show that this stop motion animation video-based learning media is "Very Feasible". This can be obtained from the score given by media experts with an average breakdown of 4.68 in the "Very Good" category with a percentage of 93.6% in the "Very Decent" category. The results of the material expert validation show an average of 4.8 in the "Very Good" category with a percentage of 96% including the "Very Eligible" category. The validation results by education practitioners with a percentage of 89.2% are included in the "Very Eligible" category. Student learning outcomes showed an increase of 40.59. Where the average value before using learning media based on stop motion animation video was 47.35 and after using learning media based on stop motion animation video was 87.94. From the results of the research that has been described, it can be concluded that learning media based on stop motion animation video in learning Thematic Theme 6 Sub-theme 2 "Heat Transfer Around Us" is feasible and effective to use.